RACHEL CHU AS LIBERAL FEMINIST IN KEVIN KWAN’S CRAZY RICH ASIANS (2013) - Suwastini, Ni Komang Arie; Banjar, I Dewa Ayu Ogik Vira Juspita; Tienty, Luh Putu Cornea Arya; Sasmita, I Made David Garcia; Nitiasih, Putu Kerti (International Journal of Language and Literature, 2020)
This study aims to identify the characterization of Rachel Chu as a liberal feminist in Crazy Rich Asians, written by Kevin Kwan, published in 2013. By employing McKee's textual analysis with liberal feminism's perspective, the present study was designed in Miles' and Huberman's interactive model of qualitative data analysis. Through the repetitive and simultaneous process of data collection, data reduction, data display, and conclusion drawing, the present study elaborates on the characterizations of Rachel Chu as an attractive, intelligent, and independent woman representing Rachel Chu as a liberal feminist. Thus, it is implied that although the novel may be fairy-tale-like in the sense that it is centered in a romantic love story with a glamorous setting of the affluent society in Singapore, the novel also inserts feminist traits that can inspire its reader to be intelligent and independent like Rachel Chu as the main character in this novel.